An Exploratory Examination of College Students' Likelihood of Reporting Sexual Assault to Police and University Officials: Results of a Self-Report Survey. Issue 22 (November 2018) - Moore, Briana M.; Baker, Thomas
Despite the growing salience of sexual assault victimizations on college campuses, reporting of such events remains low. A better understanding of what affects students' reporting behavior and to whom they are likely to report victimizations can aid in developing policies and programs that promote reporting. Using a sample of 336 college students, this study uses hypothetical scenarios to examine the factors that affect individuals' likelihood to report sexual assaults to the police and to university officials. Results show that students are significantly more likely to report sexual assaults to the police than to university officials. In addition, wanting justice, trust in police and university officials, and a desire for services are among the most consistent factors that affect students' likelihood to report to both the police and university officials.